PROBLEMATIKA PENGGUNAAN MEDIA INTERACTIVE FLAT PANEL (IFP) DALAM PEMBELAJARAN DI SD NEGERI 1 ULAK BALAM - Sari Agustina; Hetilaniar Hetilaniar; Mega Kusuma Putri (Cerdas Proklamator, 2026)
This study aims to analyze the problems of using Interactive Flat Panel (IFP) media in learning at SD Negeri 1 Ulak Balam. The increasing integration of digital technology in education has prompted many schools to adopt IFP as an interactive learning tool; however, its implementation is not without challenges. This research employed a qualitative descriptive approach, with data collected through in-depth interviews with the school principal and five teachers who were selected purposively based on their direct involvement with IFP usage. Data were analyzed using thematic analysis techniques encompassing data reduction, data presentation, and conclusion drawing. The findings reveal five major problematic themes: (1) limited infrastructure, as the school possesses only one IFP unit that must be shared among all teachers; (2) inadequate storage management, whereby the device is kept in the school office due to classroom security concerns, thereby reducing its frequency of use; (3) gaps in teacher digital competency, particularly among senior teachers who lack formal training in IFP operation; (4) technical constraints, including unstable internet connectivity and frequent power outages that disrupt digital-based lessons; and (5) suboptimal utilization, as IFP usage is limited to video playback, educational games, and YouTube content. Despite these challenges, IFP has demonstrated a positive impact on student motivation and engagement. The study concludes that sustainable optimization of IFP requires systemic support encompassing additional devices, structured training programs, improved infrastructure, and adequate storage facilities.